Monotonic laterally loaded pile testing in a stiff glacial clay till at Cowden - Byrne, B; McAdam, R; Burd, H; Beuckelaers, W; Gavin, K; Houlsby, G; Igoe, D; Jardine, R; Martin, C; Muir Wood, A; Potts, D; Skov Gretlund, J; et al. (Thomas Telford, 2019)
This paper describes the results obtained from a field testing campaign on laterally loaded monopiles conducted at Cowden, UK, where the soil consists principally of a heavily overconsolidated glacial till. These tests formed part of the PISA project on the development of improved design methods for monopile foundations for offshore wind turbines. Results obtained for monotonic loading tests on piles of three different diameters (0·273 m, 0·762 m and 2·0 m) are presented. The piles had length-to-diameter ratios (L/D) of between 3 and 10. The tests included the application of monotonic loading incorporating periods of constant load to investigate creep effects, and investigations on the influence of loading rate. Data are presented on measured bending moments and inclinations induced in the piles. Inferred data on lateral displacements of the embedded section of the piles are determined using an optimised structural model. These field data support the development of a new one-dimensional modelling approach for the design of monopile foundations for offshore wind turbines. They also form a unique database of field measurements in an overconsolidated clay, from lateral loading of piles at a vertical distance above the ground surface.